2018
DOI: 10.1002/jat.3591
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal exposure to di‐(2‐ethylhexyl)‐phthalate on fetal cardiac development in mice

Abstract: Accumulating evidence has suggested a link between maternal di-(2-ethylhexyl)-phthalate (DEHP) exposure and various developmental abnormalities. However, the evidence regarding the effect of maternal DEHP exposure on fetal cardiac development is scarce. The present study aimed to determine the effect of maternal DEHP exposure on fetal cardiac development in mice and explore the possible involved mechanism preliminarily. The C57BL mice were randomly divided into four groups: the vehicle group (corn oil, n = 10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Remarkably, L-T4 early intervention not only signi cantly increased the mRNA and protein levels of Gata4 and Nkx2-5, but also activated the BMP4/Smad4 signaling pathway in the myocardium of the offspring of SCH pregnant rats. It was reported that exposure of pregnant rats to di (2ethylhexyl) phthalate caused cardiac malformation in the offspring, which may be related to the inhibition of cardiac Gata4/mef2c/ch expression [36]. Similarly, the potential toxicity of PM2.5 to fetal heart tissue was related to the down-regulation of transcriptional factors Gata4 and Nkx2-5, which were functionally associated with to embryonic heart development and abnormalities of fetal heart structure and function [37].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, L-T4 early intervention not only signi cantly increased the mRNA and protein levels of Gata4 and Nkx2-5, but also activated the BMP4/Smad4 signaling pathway in the myocardium of the offspring of SCH pregnant rats. It was reported that exposure of pregnant rats to di (2ethylhexyl) phthalate caused cardiac malformation in the offspring, which may be related to the inhibition of cardiac Gata4/mef2c/ch expression [36]. Similarly, the potential toxicity of PM2.5 to fetal heart tissue was related to the down-regulation of transcriptional factors Gata4 and Nkx2-5, which were functionally associated with to embryonic heart development and abnormalities of fetal heart structure and function [37].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, L-T4 early intervention not only significantly increased the mRNA and protein levels of Gata4 and Nkx2-5, but also activated the BMP4/Smad4 signaling pathway in the myocardium of the offspring of SCH pregnant rats. It was reported that exposure of pregnant rats to di (2-ethylhexyl) phthalate caused cardiac malformation in the offspring, which may be related to the inhibition of cardiac Gata4/mef2c/ch expression by activating Peroxisome proliferator-activated receptor gamma (PPARγ) [36]. Similar to the results of this study, a study found that the potential toxicity of PM2.5 to fetal heart tissue was related to the down-regulation of transcriptional factors Gata4 and Nkx2-5, which were functionally associated with to embryonic heart development and abnormalities of fetal heart structure and function [37].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, L-T4 early intervention not only signi cantly increased the mRNA and protein levels of Gata4 and Nkx2-5, but also activated the BMP4/Smad4 signaling pathway in the myocardium of the offspring of SCH pregnant rats. It was reported that exposure of pregnant rats to di (2-ethylhexyl) phthalate caused cardiac malformation in the offspring, which may be related to the inhibition of cardiac Gata4/mef2c/ch expression by activating Peroxisome proliferator-activated receptor gamma (PPARγ) [36]. Similar to the results of this study, a study found that the potential toxicity of PM2.5 to fetal heart tissue was related to the down-regulation of transcriptional factors Gata4 and Nkx2-5, which were functionally associated with to embryonic heart development and abnormalities of fetal heart structure and function [37].…”
Section: Discussionmentioning
confidence: 99%